Pannexin1 channels—a potential therapeutic target in inflammation - Rusiecka, Olga M.; Tournier, Malaury; Molica, Filippo; Kwak, Brenda R. (Frontiers in Cell and Developmental Biology, 2022)
An exaggerated inflammatory response is the hallmark of a plethora of disorders. ATP is a central signaling molecule that orchestrates the initiation and resolution of the inflammatory response by enhancing activation of the inflammasome, leukocyte recruitment and activation of T cells. ATP can be released from cells through pannexin (Panx) channels, a family of glycoproteins consisting of three members, Panx1, Panx2 and Panx3. Panx1 is ubiquitously expressed and forms heptameric channels in the plasma membrane mediating paracrine and autocrine signaling. Besides its involvement in the inflammatory response, Panx1 channels have been shown to contribute to different modes of cell death (i.e., pyroptosis, necrosis and apoptosis). Both genetic ablation and pharmacological inhibition of Panx1 channels decrease inflammation in vivo and contribute to a better outcome in several animal models of inflammatory disease involving various organs, including the brain, lung, kidney and heart. Up to date, several molecules have been identified to inhibit Panx1 channels, for instance probenecid (Pbn), mefloquine (Mfq), flufenamic acid (FFA), carbenoxolone (Cbx) or mimetic peptides like 10Panx1. Unfortunately, the vast majority of these compounds lack specificity and/or serum stability, which limits their application. The recent availability of detailed structural information on the Panx1 channel from cryo-electron microscopy studies may open up innovative approaches to acquire new classes of synthetic Panx1 channel blockers with high target specificity. Selective inhibition of Panx1 channels may not only limit acute inflammatory responses but may also prove useful in chronic inflammatory diseases, thereby improving human health. Here, we reviewed the current knowledge on the role of Panx1 in the initiation and resolution of the inflammatory response, we summarized the effects of Panx1 inhibition in inflammatory pathologies and recapitulate current Panx1 channel pharmacology with an outlook towards future approaches.